تقدير الذات وعلاقته بالرفاه النفسي لدى الطالب الجامعي - إلهام يعقوب; مروة خوخو (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة الحالية إلى الكشف عن العلاقة بين تقدير الذات والرفاه النفسي لدى طلبة الجامعة بجامعة الشهيد حمه لخضر ولاية الوادي تكونت عينة الدراسة من 91 طالب من قسم علم النفس المدرسي وقسم التاريخ باستخدام مقياس تقدير الذات لكوبر سميث ومقياس الرفاه النفسي لكارول رايف كأداتين أساسيتين لجمع البيانات كما تم استخدام المنهج الوصفي بأسلوبيه العلائقي والمقارنة . وبعد المعالجة الإحصائية واستخدام الأساليب الإحصائية المناسبة توصلت دراستنا إلى : توجد علاقة ارتباطية ذات دلالة إحصائية بين تقدير الذات والرفاه النفسي لدى الطالب - توجد فروق في مستوى تقدير الذات بين التخصصين علم النفس وتاريخ - توجد فروق في مستوى الرفاه النفسي بين تخصص علم النفس المدرسي والتاريخ" "The current study aimed to explore the relationship between self-esteem and psychological well-being among university students at Chahid Hama Lakhdar University. The study sample consisted of 91 students from the Department of School Psychology and the Department of History. The Coopersmith Self-Esteem Scale and the Carol Ryff Psychological Well -Being Scale were used as the two main tools for data collection. The descriptive approach was also u sed in its correlational and comparative styles After statistical processing and the use of appropriate statistical methods, our study concluded that: There is a statistically significant correlation between self-esteem and psychological well-being among students. There are differences in the level of self-esteem between the two majors: psychology and history. There are differences in the level of psychological well-being between the majors of school psychology and history."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: الطالب الجامعي; الرفاه النفسي; تقدير الذات; Self-esteem; Psychological well-being; University student